PULMONARY AND FUNCTIONAL CAPACITY OF OBESE PATIENTS (Fiep Bulletin - online, 2016)
Objectives: To evaluate the influence of obesity on pulmonary function and perceived functional capacity in obese individuals.Methods: It was analyzed medical records of patients participating in the "Obesity Group" of the clinic HUOP - Cascavel, candidates performing bariatric surgery, which were assessed in 2014 until May 2015. The observed data were expressed in the initial evaluation of sample characterization, IMC, thoracoabdominal cirtometry, spirometry test and responses obtained in HAQ-20 questionnaire.Results: The sample included 21 patients, 18 women and three men. The degree of obesity only one patient was classified as obese grade I, five as grade II and 15 as grade III. Four patients had changes in spirometry reports, all of obstructive character. About the answers of the Health Assessment Questionnaire, HAQ-20, the areas of more influence were "stand up", "other activities" and "catch up".Conclusions: It´s possible to see that being overweight can be a factor of influence and limitation on pulmonary and functional capacity, impacting negatively on the quality of life of obese patients.
Keywords: Obesity; Spirometry; Quality of Life.